Predictors of success in primary retrograde strategy in chronic total occlusion percutaneous coronary intervention: insights from the PROGRESS‐chronic total occlusion registry. Issue 1 (26th May 2022) - Simsek, Bahadir; Kostantinis, Spyridon; Karacsonyi, Judit; Alaswad, Khaldoon; Karmpaliotis, Dimitri; Masoumi, Amirali; Jaffer, Farouc A.; Doshi, Darshan; Khatri, Jaikirshan; Poommipanit, Paul; Gorgulu, Sevket; Abi Rafeh, Nidal; et al.
Abstract: Background: An upfront (primary) retrograde strategy is often used in complex chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Methods: We examined the clinical, angiographic characteristics, and procedural outcomes of CTO PCIs that were approached with a primary retrograde strategy in the Prospective Global Registry for the Study of CTO Intervention (PROGRESS‐CTO, NCT02061436). Results: Of 10, 286 CTO PCIs performed between 2012 and 2022, a primary retrograde strategy was used in 1329 (13%) with an initial technical success of 66%, and a final success of 83%. Patients who underwent successful versus unsuccessful primary retrograde cases had similar characteristics: age (65 ± 10 vs. 65 ± 9, years, p = 0.203), men (83% vs. 87%, p = 0.066), prior PCI (71% vs. 71%, p = 0.809), and prior coronary artery bypass graft surgery (52% vs. 53%, p = 0.682). The PROGRESS‐CTO score (1.3 ± 0.9 vs. 1.6 ± 0.9, p < 0.001), air kerma radiation (3.9 ± 2.8 vs. 3.4 ± 2.6, gray, p = 0.013), and contrast use (294 ± 148 ml vs. 248 ± 128, ml, p < 0.001) were higher in the unsuccessful group, whereas the presence of interventional collaterals (95% vs. 72%, p < 0.001) and Werner collateral connection grade 2 (43% vs. 31%, p < 0.001) were higher in the successful group. On multivariable logistic regression analysis, the only variable associated with a successful primary retrograde strategy was the presence of interventional collaterals: odds ratio: 6.52 (95% confidence intervals; 3.5–12.1, p < 0.001). Conclusion: Presence of interventional collaterals is independently associated with higher success rates with a primary retrograde strategy in CTO PCI.